Cerium-containing high-coercivity rare earth permanent magnet and preparation method thereof
Rare earth permanent magnets were prepared through dual alloys, and cobalt elements were used to suppress the valence state transformation of cerium elements, forming a new main phase and rare earth-rich phase, solving the problem of reduced magnetic performance of cerium elements in rare earth permanent magnets, and achieving high coercive force and the effect of high cerium element utilization.
Patent Information
- Application Number
- CN202411793824.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-12-09
AI Technical Summary
The high content of cerium elements in existing cerium-based sintered NdFeB magnets leads to a decrease in magnetic properties. As the cerium content increases, the proportion of REFe2 phase in the magnet increases, which manifests as soft magnetic properties, limiting the widespread cerium elements in rare earth permanent magnets. use.
Rare earth permanent magnets are prepared in the form of a dual alloy, and thin strips of main and auxiliary phase alloys are prepared through vacuum speed condensation technology. Hydrogen breaks and gas flow grinds into powder and mixes under the protection of inert gas, performs magnetic field orientation molding and vacuum sintering, and adds cobalt elements. In order to inhibit the valence state of cerium element, a new main phase and rare earth-rich phase are formed through heat treatment to improve the intrinsic coercivity.
A rare earth permanent magnet with high cerium content and coercive force is achieved, which improves the utilization rate of cerium elements, reduces the cost of permanent magnet preparation, and enhances the intrinsic coercive force while maintaining magnetic properties.
Smart Images

Figure CN119252590A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of rare earth permanent magnets, in particular to a cerium-containing high-coercivity rare earth permanent magnet and a preparation method thereof. Background Art
[0002] Cerium-based sintered NdFeB magnets have been widely used. Rare earth cerium has a low price and abundant reserves. High-proportion replacement of some rare earth elements is the main development trend of the current production of rare earth permanent magnets. 14 The intrinsic magnetic properties of B phase are lower than those of Nd2Fe 14 The intrinsic magnetic properties of the B phase, where Ce is cerium, Nd is neodymium, Fe is iron, and B is boron, limit the widespread use of cerium in the preparation of NdFeB magnets. In addition, with the increase of cerium content, the proportion of REFe2 phase in the magnet will also increase. RE is a rare earth element, and the REFe2 phase is characterized by soft magnetism, which will deteriorate the magnetic properties. Therefore, the high proportion of cerium replacing rare earth elements is limited.
[0003] Therefore, based on this, the technical solution of the present invention is proposed. Summary of the invention
[0004] The purpose of the present invention is to provide a cerium-containing high-coercivity rare earth permanent magnet and a preparation method thereof, and to solve the technical problem of providing a rare earth permanent magnet with high cerium content and good coercivity.
[0005] To achieve the above object, the solution of the present invention is: a cerium-containing high coercivity rare earth permanent magnet, wherein the composition of the permanent magnet is RE in terms of mass percentage. a N b Fe 100-a-b-c-d Co c B d , RE is a combination of two or more of the rare earth elements lanthanum, cerium, praseodymium, and neodymium, and must contain cerium, the mass percentage of which is not less than 6%, N is a combination of one or more of aluminum, copper, gallium, and zirconium, Fe is iron, Co is cobalt, and B is boron; Among them, a, b, c and d respectively satisfy the following relationships: 26≤a≤35, 0.2≤b≤6.7, 0.2≤c≤7.5, 0.85≤d≤1.3.
[0006] The present invention also provides a method for preparing a cerium-containing high-coercivity rare earth permanent magnet for preparing the above-mentioned cerium-containing high-coercivity rare earth permanent magnet, wherein the permanent magnet is prepared from two raw materials, a main phase alloy and an auxiliary phase alloy, in the form of a double alloy, wherein the main phase alloy contains cerium elements and the auxiliary phase alloy contains cobalt elements.
[0007] Furthermore, the main phase alloy has a composition of (Ce a1 RE' b1-a1 ) b1 Q bal M c1 B d1 , Ce is cerium, RE' is one or more of the rare earth elements lanthanum, cerium, praseodymium, and neodymium, Q is iron, M is one or more of gallium, aluminum, copper, zirconium, and cobalt, and B is boron; Among them, a1, b1, c1, and d1 respectively satisfy the following relationships: 6≤a1≤20, 28≤b1≤31, 0≤c1≤2, 0.9≤d1≤1.1, bal is expressed as the remainder, bal=100- b1- c1- d1, the content of cerium element is a1, the content of RE' is b1- a1, and the sum of the contents of Ce and RE' is b1.
[0008] Furthermore, the auxiliary phase alloy has a composition of RE in terms of mass percentage. a2 Q" b2 M" c2 , RE" is one or more of the rare earth elements lanthanum, cerium, praseodymium, and neodymium, Q" is one or two of the elements iron and cobalt, and Q" contains at least cobalt, and M" is one or more of the elements gallium, aluminum, copper, and zirconium; Among them, a2, b2, and c2 respectively satisfy the following relations: 15≤a2≤45, 25≤b2≤55, 5≤c2≤15, a2+b2+c2=100.
[0009] Furthermore, the permanent magnet comprises (RE', Ce)2Fe 14 B main phase, (RE H , Ce)2(Fe, Co) 14 B main phase and rare earth-rich phase; Wherein, the main phase alloy contains the (RE', Ce)2Fe 14 B main phase, the main phase alloy and the auxiliary phase alloy are prepared in the form of a dual alloy, and the grain boundary is reconstructed to form the (RE H , Ce)2(Fe, Co) 14 B main phase and rare earth-rich phase, RE H Represents the rare earth elements contained after grain boundary reconstruction.
[0010] Furthermore, the following steps are included: S1: preparing a main phase alloy ribbon through a vacuum rapid solidification process, and then preparing the main phase alloy ribbon into a main phase alloy powder through a hydrogen crushing and air flow grinding process, wherein the vacuum degree of the vacuum rapid solidification process is ≤5.0-2Pa; The auxiliary phase alloy is subjected to a vacuum rapid solidification process to prepare an auxiliary phase alloy ribbon, and then the auxiliary phase alloy ribbon is prepared into an auxiliary phase alloy powder by hydrogen cracking and air flow grinding, wherein the vacuum degree of the vacuum rapid solidification process is ≤5.0-2Pa; S2: uniformly mixing the main phase alloy powder and the auxiliary phase alloy powder under the protection of an inert gas to form a mixed powder, wherein the auxiliary phase alloy powder accounts for 3% to 10% of the total mass of the mixed powder; S3: Orienting and molding the obtained mixed powder in a magnetic field of 1.5-2.5 T to obtain a green body; S4: vacuum-packaging the obtained green body, cold isostatically pressing at 180-220 MPa, and placing it in a vacuum sintering furnace for sintering and heat treatment to obtain the permanent magnet.
[0011] Furthermore, the sintering temperature is 950-1080° C., and the sintering time is 3-5 hours.
[0012] Furthermore, the primary aging temperature range of the heat treatment is 700-920°C, and the time is 3-5 hours, and the secondary aging temperature range of the heat treatment is 400-700°C, and the time is 3-5 hours.
[0013] Furthermore, the thickness of the main phase alloy strip is 0.2 to 0.5 mm.
[0014] Furthermore, the main phase alloy powder is 3-5 μm, and the auxiliary phase alloy powder is 3-5 μm.
[0015] After adopting the above scheme, the beneficial effects of the present invention are: (1) The permanent magnet prepared by the present invention has a high cerium content and a low heavy rare earth element content, and the permanent magnet also has a high coercive force, which can improve the utilization rate of the abundant cerium element while maintaining the magnetic properties of the permanent magnet, thereby reducing the cost of preparing the permanent magnet.
[0016] (2) The auxiliary phase alloy contains cobalt. The permanent magnet is prepared by combining the main phase alloy and the auxiliary phase alloy in the form of a dual alloy. During the preparation process, the cobalt element in the auxiliary phase alloy can inhibit the valence state transformation of the cerium element and promote the entry of the cerium element into the main phase. As the cerium content increases, the precipitation of the CeFe2 phase can be reduced, and the RE'Fe2 phase in the main phase alloy can be melted during liquid phase sintering, reducing the volume share of the RE'Fe2 phase, which can effectively reduce the deterioration of the magnet performance caused by the soft magnetic properties of the RE'Fe2 phase. During the preparation process of the main phase alloy and the auxiliary phase alloy in the form of a dual alloy, the grain boundary is reconstructed to form a new main phase and a rare earth-rich phase, increasing the volume share of the main phase in the permanent magnet. The formation of the rare earth-rich phase increases the grain boundary width, and at the same time, the demagnetization exchange coupling effect is enhanced, thereby increasing the intrinsic coercive force of the permanent magnet. Under the premise of ensuring the magnetic properties of the permanent magnet, the cerium element can replace part of the rare earth metal to form a rare earth permanent magnet with a high cerium content and high coercive force. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is a microstructure diagram of the rare earth permanent magnet prepared in Comparative Example 10.
[0018] Figure 2 This is a microstructure diagram of the rare earth permanent magnet prepared in Example 3.
[0019] Figure 3 This is a microstructure diagram of the rare earth permanent magnet prepared in Comparative Example 12.
[0020] Figure 4 This is a microstructure diagram of the rare earth permanent magnet prepared in Example 5. DETAILED DESCRIPTION
[0021] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described in detail below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other implementation methods obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0022] The present invention provides a cerium-containing high-coercivity rare earth permanent magnet, wherein the permanent magnet has a composition of RE in terms of mass percentage. a N b Fe 100-a-b-c-d Co c B d RE is a combination of two or more of the rare earth elements lanthanum, cerium, praseodymium, and neodymium, and must contain cerium, with the mass percentage of cerium not less than 6%, that is, RE a N b Fe 100-a-b-c-d Coc B d The total mass of the cerium element is not less than 6 parts, N is one or more combinations of aluminum, copper, gallium, and zirconium, Fe is iron, Co is cobalt, and B is boron. In other embodiments, N can also be one or more combinations of aluminum, copper, gallium, zirconium, zinc, vanadium, titanium, nickel, and chromium; Among them, a, b, c and d respectively satisfy the following relationships: 26≤a≤35, 0.2≤b≤6.7, 0.2≤c≤7.5, 0.85≤d≤1.3.
[0023] The present invention also provides a method for preparing a cerium-containing high-coercivity rare earth permanent magnet for preparing the above-mentioned cerium-containing high-coercivity rare earth permanent magnet, wherein the permanent magnet is prepared from two raw materials, a main phase alloy and an auxiliary phase alloy, in the form of a double alloy, wherein the main phase alloy contains a cerium element, and the auxiliary phase alloy contains a cobalt element. Specifically, preparing the rare earth permanent magnet in the form of a double alloy is an existing method for preparing a permanent magnet, and includes sintering and heat treatment processes.
[0024] Wherein, the main phase alloy has the following composition by mass percentage: a1 RE' b1-a1 ) b1 Q bal M c1 B d1 , Ce is cerium, RE' is one or more of the rare earth elements lanthanum, cerium, praseodymium, and neodymium, Q is iron, M is one or more of gallium, aluminum, copper, zirconium, and cobalt, B is boron, and in other embodiments, M can also be one or more of gallium, aluminum, copper, zirconium, titanium, niobium, vanadium, chromium, cobalt, and nickel; wherein a1, b1, c1, and d1 respectively satisfy the following relationships: 6≤a1≤20, 28≤b1≤31, 0≤c1≤2, 0.9≤d1≤1.1, bal is represented as the remainder, bal=100- b1- c1- d1, the content of cerium is a1, the content of RE' is b1- a1, and the sum of the contents of Ce and RE' is b1.
[0025] The auxiliary phase alloy has a composition of RE" in terms of mass percentage. a2 Q" b2 M" c2 , RE" is one or more of the rare earth elements lanthanum, cerium, praseodymium, and neodymium, Q" is one or two of the iron and cobalt elements, and Q" contains at least cobalt, M" is one or more of the gallium, aluminum, copper, and zirconium elements. In other embodiments, M" can also be one or more of the gallium, aluminum, copper, zirconium, titanium, and niobium elements; wherein a2, b2, and c2 respectively satisfy the following relationships: 15≤a2≤45, 25≤b2≤55, 5≤c2≤15, and a2+b2+c2=100.
[0026] The method for preparing the cerium-containing high-coercivity rare earth permanent magnet comprises the following steps: S1: preparing a main phase alloy ribbon through a vacuum rapid solidification process, and then preparing the main phase alloy ribbon into a main phase alloy powder through a hydrogen crushing and air flow grinding process, wherein the vacuum degree of the vacuum rapid solidification process is ≤5.0-2Pa; The auxiliary phase alloy is subjected to a vacuum rapid solidification process to prepare an auxiliary phase alloy ribbon, and then the auxiliary phase alloy ribbon is prepared into an auxiliary phase alloy powder by hydrogen cracking and air flow grinding, wherein the vacuum degree of the vacuum rapid solidification process is ≤5.0-2Pa; S2: uniformly mixing the main phase alloy powder and the auxiliary phase alloy powder under the protection of an inert gas to form a mixed powder, wherein the auxiliary phase alloy powder accounts for 3% to 10% of the total mass of the mixed powder; S3: Orienting and molding the obtained mixed powder in a magnetic field of 1.5-2.5 T to obtain a green body; S4: vacuum-packaging the obtained green body, cold isostatically pressing at 180-220 MPa, and placing it in a vacuum sintering furnace for sintering and heat treatment to obtain the permanent magnet.
[0027] Preferably, the sintering temperature is 950-1080°C, the sintering time is 3-5h, the primary aging temperature range of heat treatment is 700-920°C, the time is 3-5h, and the secondary aging temperature range of heat treatment is 400-700°C, the time is 3-5h.
[0028] Preferably, the thickness of the main phase alloy strip is 0.2 to 0.5 mm.
[0029] Preferably, the main phase alloy powder is 3-5 μm, and the auxiliary phase alloy powder is 3-5 μm.
[0030] In this specific embodiment, the permanent magnet comprises (RE', Ce)2Fe 14 B main phase, (RE, Ce)2(Fe, Co) 14 B main phase and rare earth-rich phase, wherein the main phase alloy contains the (RE', Ce)2Fe 14 B main phase, the main phase alloy and the auxiliary phase alloy are prepared in the form of a dual alloy, and the grain boundary reconstruction is carried out during the sintering heat treatment process to form the new (RE H , Ce)2(Fe, Co) 14B main phase and rare earth-rich phase, wherein RE' is the rare earth element in the main phase alloy, specifically one or more of the other lanthanide rare earth elements except heavy rare earth elements dysprosium and terbium. Since the auxiliary phase alloy also includes rare earth element RE", and RE' and RE" may be different, the rare earth elements in the new main phase and rare earth-rich phase formed after sintering heat treatment will also be different. The rare earth elements in the new main phase and rare earth-rich phase are expressed by RE H To indicate, to distinguish.
[0031] In addition, the main phase alloy also includes RE'Fe2 phase. Since the melting point of RE'Fe2 phase is lower than the sintering process temperature of the permanent magnet, it can melt to form a liquid phase during the sintering process and reorganize with the auxiliary phase alloy to form the new (RE H , Ce)2(Fe, Co) 14 B main phase, increasing the volume fraction of the main phase, effectively reducing the volume fraction of RE'Fe2 phase, and also reducing the tendency of CeFe2 phase precipitation caused by increasing Ce element content. Figure 1-4 It can be seen that the proportion of CeFe2 phase in the permanent magnet containing cobalt prepared by the dual alloy form decreases, while the CeFe2 phase in the permanent magnet without cobalt prepared by the dual alloy form is significantly more, which can reduce the deterioration of the magnetic properties of the permanent magnet caused by the soft magnetic properties of CeFe2 phase and other RE'Fe2 phases, and form a rare earth-rich phase during the heat treatment aging process. The rare earth-rich phase is specifically RE H 6(Fe, M')14 phase can increase the grain boundary width, promote the diffusion of Ce elements into the main phase, replace part of the rare earth elements, and enhance the demagnetization exchange coupling effect, thereby improving the remanence and intrinsic coercivity of the permanent magnet. H In the 6(Fe, M')14 phase, RE H is a rare earth element, and M' is one or both of aluminum and gallium.
[0032] Example 1 Step S1: According to the main phase alloy composition (Ce6PrNd 23.5 ) 29.5 Fe bal Cu 0.2 Zr 0.3 B1 is used for batching, and a main phase alloy ribbon is prepared by a rapid solidification process in a vacuum induction melting furnace with a vacuum degree of ≤5.0-2Pa, and the average thickness of the ribbon is 0.26mm. The main phase alloy ribbon is then prepared into a main phase alloy powder with an average particle size of 4.2μm by hydrogen crushing and air flow grinding processes; According to the auxiliary phase alloy composition PrNd 45 Fe 30 Co 15Ga5 was used as the material, and the auxiliary phase alloy ribbon was prepared by the rapid solidification process, and then the auxiliary phase alloy ribbon was prepared into auxiliary phase alloy powder with an average particle size of 3.5μm through hydrogen rupture and air flow grinding process; Wherein, PrNd is a praseodymium-neodymium alloy, and bal represents the balance; Step S2: The main phase alloy powder and the auxiliary phase alloy powder are uniformly mixed in a ratio of 95:5 under the protection of inert gas to form a mixed powder. The nominal composition of the obtained mixed powder is Ce 5.7 PcqI 24.575 Cu 0.19 Ga 0.25 Co 0.75 Zr 0.285 B 0.95 Fe b al ; Step S3: Orienting and pressing the obtained mixed powder in a 2T magnetic field to obtain a green body; Step S4: vacuum package the obtained green body, cold isostatically press at 200 MPa, hold the pressure for 30 seconds, and then put it into a vacuum sintering furnace for sintering and heat treatment. The sintering temperature is 1050°C and the sintering time is 6 hours. The primary heat treatment temperature is 900°C and the time is 3 hours. The secondary aging heat treatment temperature is 500°C and the time is 5 hours.
[0033] Example 2 Step S1: According to the main phase alloy composition (Ce8PrNd 21.5 ) 29.5 Fe bal Cu 0.2 Zr 0.3 B1 is used for batching, and a main phase alloy ribbon is prepared by a rapid solidification process in a vacuum induction melting furnace with a vacuum degree of ≤5.0-2Pa, and the average thickness of the ribbon is 0.26mm. The main phase alloy ribbon is then prepared into a main phase alloy powder with an average particle size of 4.2μm by hydrogen crushing and air flow grinding processes; According to the auxiliary phase alloy composition PrNd 45 Fe 30 Co 15 Ga5 was used as the material, and the auxiliary phase alloy ribbon was prepared by the rapid solidification process, and then the auxiliary phase alloy ribbon was prepared into auxiliary phase alloy powder with an average particle size of 3.5μm through hydrogen rupture and air flow grinding process; Wherein, PrNd is a praseodymium-neodymium alloy, and bal represents the balance; Step S2: The main phase alloy powder and the auxiliary phase alloy powder are uniformly mixed in a ratio of 95:5 under the protection of inert gas to form a mixed powder. The nominal composition of the obtained mixed powder is Ce 7.6 PcqI 22.675 Cu 0.19 Ga 0.25Co 0.75 Zr 0.285 B 0.95 Fe b al ; Step S3: Orienting and pressing the obtained mixed powder in a 2T magnetic field to obtain a green body; Step S4: vacuum package the obtained green body, cold isostatically press at 200 MPa, hold the pressure for 30 seconds, and then put it into a vacuum sintering furnace for sintering and heat treatment. The sintering temperature is 1040°C and the sintering time is 6 hours. The primary heat treatment temperature is 900°C and the time is 3 hours. The secondary aging heat treatment temperature is 630°C and the time is 5 hours.
[0034] Example 3 Step S1: According to the main phase alloy composition (Ce 10 PcqI 19.5 ) 29.5 Fe bal Cu 0.2 Zr 0.3 B1 is used for batching, and a main phase alloy ribbon is prepared by a rapid solidification process in a vacuum induction melting furnace with a vacuum degree of ≤5.0-2Pa, and the average thickness of the ribbon is 0.26mm. The main phase alloy ribbon is then prepared into a main phase alloy powder with an average particle size of 4.2μm by hydrogen crushing and air flow grinding processes; According to the auxiliary phase alloy composition PrNd 45 Fe 30 Co 15 Ga5 was used as the material, and the auxiliary phase alloy ribbon was prepared by the rapid solidification process, and then the auxiliary phase alloy ribbon was prepared into auxiliary phase alloy powder with an average particle size of 3.5μm through hydrogen rupture and air flow grinding process; Wherein, PrNd is a praseodymium-neodymium alloy, and bal represents the balance; Step S2: The main phase alloy powder and the auxiliary phase alloy powder are uniformly mixed in a ratio of 95:5 under the protection of inert gas to form a mixed powder. The nominal composition of the obtained mixed powder is Ce 9.5 PcqI 20.775 Cu 0.19 Ga 0.25 Co 0.75 Zr 0.285 B 0.95 Fe b al ; Step S3: Orienting and pressing the obtained mixed powder in a 2T magnetic field to obtain a green body; Step S4: vacuum-packaging the obtained green body, cold isostatic pressing at 200 MPa, holding the pressure for 30 seconds, and then placing it in a vacuum sintering furnace for sintering and heat treatment. The sintering temperature is 1040°C, the sintering time is 6 hours, the primary heat treatment temperature is 900°C, the time is 3 hours, and the secondary aging heat treatment temperature is 630°C, and the time is 5 hours. The BSE image of the rare earth permanent magnet prepared in this specific embodiment is as follows: Figure 2 As shown in the figure, BSE image is the abbreviation of backscattered electron image (Backscattered Electrons), which is a microscopic structure image of a scanning electron microscope (Scanning Electron Microscope).
[0035] Example 4 Step S1: According to the main phase alloy composition (Ce 12 PcqI 17.5 ) 29.5 Fe bal Cu 0.2 Zr 0.3 B1 is used for batching, and a main phase alloy ribbon is prepared by a rapid solidification process in a vacuum induction melting furnace with a vacuum degree of ≤5.0-2Pa, and the average thickness of the ribbon is 0.26mm. The main phase alloy ribbon is then prepared into a main phase alloy powder with an average particle size of 4.2μm by hydrogen crushing and air flow grinding processes; According to the auxiliary phase alloy composition PrNd 45 Fe 30 Co 15 Ga5 was used as the material, and the auxiliary phase alloy ribbon was prepared by the rapid solidification process, and then the auxiliary phase alloy ribbon was prepared into auxiliary phase alloy powder with an average particle size of 3.5μm through hydrogen rupture and air flow grinding process; Wherein, PrNd is a praseodymium-neodymium alloy, and bal represents the balance; Step S2: The main phase alloy powder and the auxiliary phase alloy powder are uniformly mixed in a ratio of 95:5 under the protection of inert gas to form a mixed powder. The nominal composition of the obtained mixed powder is Ce 11.4 PcqI 18.875 Cu 0.19 Ga 0.25 Co 0.75 Zr 0.285 B 0.95 Fe bal ; Step S3: Orienting and pressing the obtained mixed powder in a 2T magnetic field to obtain a green body; Step S4: vacuum package the obtained green body, cold isostatically press at 200 MPa, hold the pressure for 30 seconds, and then put it into a vacuum sintering furnace for sintering and heat treatment. The sintering temperature is 1030°C and the sintering time is 6 hours. The primary heat treatment temperature is 900°C and the time is 3 hours. The secondary aging heat treatment temperature is 630°C and the time is 5 hours.
[0036] Example 5 Step S1: According to the main phase alloy composition (Ce 20 PcqI 9.5 ) 29.5 Fe bal Cu 0.2 Zr 0.3 B1 is used for batching, and a main phase alloy ribbon is prepared by a rapid solidification process in a vacuum induction melting furnace with a vacuum degree of ≤5.0-2Pa, and the average thickness of the ribbon is 0.26mm. The main phase alloy ribbon is then prepared into a main phase alloy powder with an average particle size of 4.2μm by hydrogen crushing and air flow grinding processes; According to the auxiliary phase alloy composition PrNd 45 Fe 20 Co 25 Ga5 was used as the material, and the auxiliary phase alloy ribbon was prepared by the rapid solidification process, and then the auxiliary phase alloy ribbon was prepared into auxiliary phase alloy powder with an average particle size of 3.5 μm through hydrogen rupture and air flow grinding process; Wherein, PrNd is a praseodymium-neodymium alloy, and bal represents the balance; Step S2: The main phase alloy powder and the auxiliary phase alloy powder are uniformly mixed in a ratio of 95:5 under the protection of inert gas to form a mixed powder. The nominal composition of the obtained mixed powder is Ce 19 PcqI 11.275 Cu 0.19 Ga 0.25 Co 1.25 Zr 0.285 B 0.95 Fe bal ; Step S3: Orienting and pressing the obtained mixed powder in a 2T magnetic field to obtain a green body; Step S4: vacuum package the obtained green body, cold isostatically press at 200 MPa, hold the pressure for 30 seconds, and then put it into a vacuum sintering furnace for sintering and heat treatment. The sintering temperature is 1020°C, the sintering time is 6 hours, the primary heat treatment temperature is 900°C, the time is 3 hours, and the secondary aging heat treatment temperature is 630°C, the time is 5 hours. The BSE image of the rare earth permanent magnet prepared in this specific embodiment is as follows: Figure 4 shown.
[0037] Example 6 Step S1: According to the main phase alloy composition (Ce 10 PcqI19.5 ) 29.5 Fe bal Cu 0.2 Zr 0.3 B1 is used for batching, and a main phase alloy ribbon is prepared by a rapid solidification process in a vacuum induction melting furnace with a vacuum degree of ≤5.0-2Pa, and the average thickness of the ribbon is 0.26mm. The main phase alloy ribbon is then prepared into a main phase alloy powder with an average particle size of 4.2μm by hydrogen crushing and air flow grinding processes; According to the auxiliary phase alloy composition PrNd 45 Fe 20 Co 25 Ga5 was used as the material, and the auxiliary phase alloy ribbon was prepared by the rapid solidification process, and then the auxiliary phase alloy ribbon was prepared into auxiliary phase alloy powder with an average particle size of 3.5μm through hydrogen rupture and air flow grinding process; Wherein, PrNd is a praseodymium-neodymium alloy, and bal represents the balance; Step S2: The main phase alloy powder and the auxiliary phase alloy powder are uniformly mixed in a ratio of 95:5 under the protection of inert gas to form a mixed powder. The nominal composition of the obtained mixed powder is Ce 9.5 PcqI 20.775 Cu 0.19 Ga 0.25 Co 1.25 Zr 0.285 B 0.95 Fe b al ; Step S3: Orienting and pressing the obtained mixed powder in a 2T magnetic field to obtain a green body; Step S4: vacuum package the obtained green body, cold isostatically press at 200 MPa, hold the pressure for 30 seconds, and then put it into a vacuum sintering furnace for sintering and heat treatment. The sintering temperature is 1040°C and the sintering time is 6 hours. The primary heat treatment temperature is 900°C and the time is 3 hours. The secondary aging heat treatment temperature is 630°C and the time is 5 hours.
[0038] Example 7 Step S1: According to the main phase alloy composition (Ce 10 PcqI 19.5 ) 29.5 Fe bal Cu 0.2 Zr 0.3 B1 is used for batching, and a main phase alloy ribbon is prepared by a rapid solidification process in a vacuum induction melting furnace with a vacuum degree of ≤5.0-2Pa, and the average thickness of the ribbon is 0.26mm. The main phase alloy ribbon is then prepared into a main phase alloy powder with an average particle size of 4.2μm by hydrogen crushing and air flow grinding processes; According to the auxiliary phase alloy composition PrNd 45 Fe 10Co 35 Ga5 was used as the material, and the auxiliary phase alloy ribbon was prepared by the rapid solidification process, and then the auxiliary phase alloy ribbon was prepared into auxiliary phase alloy powder with an average particle size of 3.5μm through hydrogen rupture and air flow grinding process; Wherein, PrNd is a praseodymium-neodymium alloy, and bal represents the balance; Step S2: The main phase alloy powder and the auxiliary phase alloy powder are uniformly mixed in a ratio of 95:5 under the protection of inert gas to form a mixed powder. The nominal composition of the obtained mixed powder is Ce 9.5 PcqI 20.775 Cu 0.19 Ga 0.25 Co 1.75 Zr 0.285 B 0.95 Fe b al ; Step S3: Orienting and pressing the obtained mixed powder in a 2T magnetic field to obtain a green body; Step S4: vacuum package the obtained green body, cold isostatically press at 200 MPa, hold the pressure for 30 seconds, and then put it into a vacuum sintering furnace for sintering and heat treatment. The sintering temperature is 1040°C and the sintering time is 6 hours. The primary heat treatment temperature is 900°C and the time is 3 hours. The secondary aging heat treatment temperature is 630°C and the time is 5 hours.
[0039] Comparative Example 1 The nominal composition of the mixed powder in step 2 of Example 1 is Ce 5.7 PcqI 24.575 Cu 0.19 Ga 0.25 Co 0.75 Zr 0.285 B 0.9 5Fe bal After the ingredients are prepared, they are directly melted into thin strips with an average thickness of 0.26 mm. They are then crushed by hydrogen and ground by air flow to obtain powders with an average particle size of 4.2 μm. Oriented pressing is carried out under a 2T magnetic field, with an isostatic pressing pressure of 200 MPa and a holding time of 30 s. The billet sintering temperature is 1050°C and the sintering time is 6 h. The primary heat treatment temperature is 900°C and the time is 3 h. The secondary aging heat treatment temperature is 500°C and the time is 5 h.
[0040] Comparative Example 2 The nominal composition of the mixed powder in step 2 of Example 2 is Ce 7.6 PcqI 22.675 Cu 0.19 Ga 0.25 Co 0.75 Zr 0.285 B 0.9 5Fe balAfter the ingredients are prepared, they are directly melted into thin strips with an average thickness of 0.26 mm. They are then crushed by hydrogen and ground by air flow to obtain powders with an average particle size of 4.2 μm. Oriented pressing is carried out under a 2T magnetic field, with an isostatic pressing pressure of 200 MPa and a holding time of 30 s. The billet sintering temperature is 1040°C and the sintering time is 6 h. The primary heat treatment temperature is 900°C and the time is 3 h. The secondary aging heat treatment temperature is 630°C and the time is 5 h.
[0041] Comparative Example 3 The nominal composition of the mixed powder in step 2 of Example 3 is Ce 9.5 PcqI 20.775 Cu 0.19 Ga 0.25 Co 0.75 Zr 0.285 B 0.9 5Fe bal After the ingredients are prepared, they are directly melted into thin strips with an average thickness of 0.26 mm. They are then crushed by hydrogen and ground by air flow to obtain powders with an average particle size of 4.2 μm. Oriented pressing is carried out under a 2T magnetic field, with an isostatic pressing pressure of 200 MPa and a holding time of 30 s. The billet sintering temperature is 1040°C and the sintering time is 6 h. The primary heat treatment temperature is 900°C and the time is 3 h. The secondary aging heat treatment temperature is 630°C and the time is 5 h.
[0042] Comparative Example 4 The nominal composition of the mixed powder in step 2 of Example 4 is Ce 11.4 PcqI 18.875 Cu 0.19 Ga 0.25 Co 0.75 Zr 0.28 5B 0.95 Fe bal After the ingredients are prepared, they are directly melted into thin strips with an average thickness of 0.26 mm. They are then crushed by hydrogen and ground by air flow to obtain powders with an average particle size of 4.2 μm. Oriented pressing is carried out under a 2T magnetic field, with an isostatic pressing pressure of 200 MPa and a holding time of 30 s. The billet sintering temperature is 1030°C and the sintering time is 6 h. The primary heat treatment temperature is 900°C and the time is 3 h. The secondary aging heat treatment temperature is 630°C and the time is 5 h.
[0043] Comparative Example 5 The nominal composition of the mixed powder in step 2 of Example 5 is Ce 19 PcqI 11.275 Cu 0.19 Ga 0.25 Co 1.25 Zr 0.285 B 0.95 Fe balAfter batching, it is directly melted into a thin strip with an average thickness of 0.26 mm. It is then crushed by hydrogen and ground by air flow to obtain a powder with an average particle size of 4.2 μm. It is oriented and pressed under a 2T magnetic field, with an isostatic pressing pressure of 200 MPa and a holding time of 30 s. The billet sintering temperature is 1020°C and the sintering time is 6 h. The primary heat treatment temperature is 900°C and the time is 3 h. The secondary aging heat treatment temperature is 630°C and the time is 5 h.
[0044] Comparative Example 6 The nominal composition of the mixed powder in step 2 of Example 6 is Ce 9.5 PcqI 20.775 Cu 0.19 Ga 0.25 Co 1.75 Zr 0.285 B 0.9 5Fe bal After the ingredients are prepared, they are directly melted into thin strips with an average thickness of 0.26 mm. They are then crushed by hydrogen and ground by air flow to obtain powders with an average particle size of 4.2 μm. Oriented pressing is carried out under a 2T magnetic field, with an isostatic pressing pressure of 200 MPa and a holding time of 30 s. The billet sintering temperature is 1040°C and the sintering time is 6 h. The primary heat treatment temperature is 900°C and the time is 3 h. The secondary aging heat treatment temperature is 630°C and the time is 5 h.
[0045] Comparative Example 7 The nominal composition of the mixed powder in step 2 of Example 7 is Ce 9.5 PcqI 20.775 Cu 0.19 Ga 0.25 Co 1.25 Zr 0.285 B 0.9 5Fe bal After the ingredients are prepared, they are directly melted into thin strips with an average thickness of 0.26 mm. They are then crushed by hydrogen and ground by air flow to obtain powders with an average particle size of 4.2 μm. Oriented pressing is carried out under a 2T magnetic field, with an isostatic pressing pressure of 200 MPa and a holding time of 30 s. The billet sintering temperature is 1040°C and the sintering time is 6 h. The primary heat treatment temperature is 900°C and the time is 3 h. The secondary aging heat treatment temperature is 630°C and the time is 5 h.
[0046] Comparative Example 8 Step S1: According to the main phase alloy composition (Ce6PrNd 23.5 ) 29.5 Fe bal Cu 0.2 Zr 0.3B1 is used for batching, and a main phase alloy ribbon is prepared by a rapid solidification process in a vacuum induction melting furnace with a vacuum degree of ≤5.0-2Pa, and the average thickness of the ribbon is 0.26mm. The main phase alloy ribbon is then prepared into a main phase alloy powder with an average particle size of 4.2μm by hydrogen crushing and air flow grinding processes; According to the auxiliary phase alloy composition PrNd 45 Fe 45 Ga5 was used as the material, and the auxiliary phase alloy ribbon was prepared by the rapid solidification process, and then the auxiliary phase alloy ribbon was prepared into auxiliary phase alloy powder with an average particle size of 3.5 μm through hydrogen rupture and air flow grinding process; Wherein, PrNd is a praseodymium-neodymium alloy, and bal represents the balance; Step S2: The main phase alloy powder and the auxiliary phase alloy powder are uniformly mixed in a ratio of 95:5 under the protection of inert gas to form a mixed powder. The nominal composition of the obtained mixed powder is Ce 5.7 PcqI 24.575 Cu 0.19 Ga 0.25 Zr 0.285 B 0.95 Fe bal ; Step S3: Orienting and pressing the obtained mixed powder in a 2T magnetic field to obtain a green body; Step S4: vacuum package the obtained green body, cold isostatically press at 200 MPa, hold the pressure for 30 seconds, and then put it into a vacuum sintering furnace for sintering and heat treatment. The sintering temperature is 1050°C and the sintering time is 6 hours. The primary heat treatment temperature is 900°C and the time is 3 hours. The secondary aging heat treatment temperature is 500°C and the time is 5 hours.
[0047] Comparative Example 9 Step S1: According to the main phase alloy composition (Ce8PrNd 21.5 ) 29.5 Fe bal Cu 0.2 Zr 0.3 B1 is used for batching, and a main phase alloy ribbon is prepared by a rapid solidification process in a vacuum induction melting furnace with a vacuum degree of ≤5.0-2Pa, and the average thickness of the ribbon is 0.26mm. The main phase alloy ribbon is then prepared into a main phase alloy powder with an average particle size of 4.2μm by hydrogen crushing and air flow grinding processes; According to the auxiliary phase alloy composition PrNd 45 Fe 45 Ga5 was used as the material, and the auxiliary phase alloy ribbon was prepared by the rapid solidification process, and then the auxiliary phase alloy ribbon was prepared into auxiliary phase alloy powder with an average particle size of 3.5μm through hydrogen rupture and air flow grinding process; Wherein, PrNd is a praseodymium-neodymium alloy, and bal represents the balance; Step S2: The main phase alloy powder and the auxiliary phase alloy powder are uniformly mixed in a ratio of 95:5 under the protection of inert gas to form a mixed powder. The nominal composition of the obtained mixed powder is Ce 7.6 PcqI 22.675 Cu 0.19 Ga 0.25 Zr 0.285 B 0.95 Fe bal ; Step S3: Orienting and pressing the obtained mixed powder in a 2T magnetic field to obtain a green body; Step S4: vacuum package the obtained green body, cold isostatically press at 200 MPa, hold the pressure for 30 seconds, and then put it into a vacuum sintering furnace for sintering and heat treatment. The sintering temperature is 1040°C and the sintering time is 6 hours. The primary heat treatment temperature is 900°C and the time is 3 hours. The secondary aging heat treatment temperature is 630°C and the time is 5 hours.
[0048] Comparative Example 10 Step S1: According to the main phase alloy composition (Ce 10 PcqI 19.5 ) 29.5 Fe bal Cu 0.2 Zr 0.3 B1 is used for batching, and a main phase alloy ribbon is prepared by a rapid solidification process in a vacuum induction melting furnace with a vacuum degree of ≤5.0-2Pa, and the average thickness of the ribbon is 0.26mm. The main phase alloy ribbon is then prepared into a main phase alloy powder with an average particle size of 4.2μm by hydrogen crushing and air flow grinding processes; According to the auxiliary phase alloy composition PrNd 45 Fe 45 Ga5 was used as the material, and the auxiliary phase alloy ribbon was prepared by the rapid solidification process, and then the auxiliary phase alloy ribbon was prepared into auxiliary phase alloy powder with an average particle size of 3.5 μm through hydrogen rupture and air flow grinding process; Wherein, PrNd is a praseodymium-neodymium alloy, and bal represents the balance; Step S2: The main phase alloy powder and the auxiliary phase alloy powder are uniformly mixed in a ratio of 95:5 under the protection of inert gas to form a mixed powder. The nominal composition of the obtained mixed powder is Ce 9.5 PcqI 20.775 Cu 0.19 Ga 0.25 Zr 0.285 B 0.95 Fe bal ; Step S3: Orienting and pressing the obtained mixed powder in a 2T magnetic field to obtain a green body; Step S4: vacuum-packaging the obtained green body, cold isostatic pressing at 200 MPa, holding the pressure for 30 seconds, and then placing it in a vacuum sintering furnace for sintering and heat treatment. The sintering temperature is 1040°C, the sintering time is 6 hours, the primary heat treatment temperature is 900°C, the time is 3 hours, and the secondary aging heat treatment temperature is 630°C, and the time is 5 hours. The BSE image of the rare earth permanent magnet prepared in this specific embodiment is as follows: Figure 1 shown.
[0049] Comparative Example 11 Step S1: According to the main phase alloy composition (Ce 12 PcqI 17.5 ) 29.5 Fe bal Cu 0.2 Zr 0.3 B1 is used for batching, and a main phase alloy ribbon is prepared by a rapid solidification process in a vacuum induction melting furnace with a vacuum degree of ≤5.0-2Pa, and the average thickness of the ribbon is 0.26mm. The main phase alloy ribbon is then prepared into a main phase alloy powder with an average particle size of 4.2μm by hydrogen crushing and air flow grinding processes; According to the auxiliary phase alloy composition PrNd 45 Fe 45 Ga5 was used as the material, and the auxiliary phase alloy ribbon was prepared by the rapid solidification process, and then the auxiliary phase alloy ribbon was prepared into auxiliary phase alloy powder with an average particle size of 3.5μm through hydrogen rupture and air flow grinding process; Wherein, PrNd is a praseodymium-neodymium alloy, and bal represents the balance; Step S2: The main phase alloy powder and the auxiliary phase alloy powder are uniformly mixed in a ratio of 95:5 under the protection of inert gas to form a mixed powder. The nominal composition of the obtained mixed powder is Ce 11.4 PcqI 18.875 Cu 0.19 Ga 0.25 Zr 0.285 B 0.95 Fe bal ; Step S3: Orienting and pressing the obtained mixed powder in a 2T magnetic field to obtain a green body; Step S4: vacuum package the obtained green body, cold isostatically press at 200 MPa, hold the pressure for 30 seconds, and then put it into a vacuum sintering furnace for sintering and heat treatment. The sintering temperature is 1030°C and the sintering time is 6 hours. The primary heat treatment temperature is 900°C and the time is 3 hours. The secondary aging heat treatment temperature is 630°C and the time is 5 hours.
[0050] Comparative Example 12 Step S1: According to the main phase alloy composition (Ce 20 PcqI 9.5 ) 29.5 Febal Cu 0.2 Zr 0.3 B1 is used for batching, and a main phase alloy ribbon is prepared by a rapid solidification process in a vacuum induction melting furnace with a vacuum degree of ≤5.0-2Pa, and the average thickness of the ribbon is 0.26mm. The main phase alloy ribbon is then prepared into a main phase alloy powder with an average particle size of 4.2μm by hydrogen crushing and air flow grinding processes; According to the auxiliary phase alloy composition PrNd 45 Fe 45 Ga5 was used as the material, and the auxiliary phase alloy ribbon was prepared by the rapid solidification process, and then the auxiliary phase alloy ribbon was prepared into auxiliary phase alloy powder with an average particle size of 3.5μm through hydrogen rupture and air flow grinding process; Wherein, PrNd is a praseodymium-neodymium alloy, and bal represents the balance; Step S2: The main phase alloy powder and the auxiliary phase alloy powder are uniformly mixed in a ratio of 95:5 under the protection of inert gas to form a mixed powder. The nominal composition of the obtained mixed powder is Ce 19 PcqI 11.275 Cu 0.19 Ga 0.25 Zr 0.285 B 0.95 Fe bal ; Step S3: Orienting and pressing the obtained mixed powder in a 2T magnetic field to obtain a green body; Step S4: vacuum package the obtained green body, cold isostatically press at 200 MPa, hold the pressure for 30 seconds, and then put it into a vacuum sintering furnace for sintering and heat treatment. The sintering temperature is 1020°C, the sintering time is 6 hours, the primary heat treatment temperature is 900°C, the time is 3 hours, and the secondary aging heat treatment temperature is 630°C, the time is 5 hours. The BSE image of the rare earth permanent magnet prepared in this specific embodiment is as follows: Figure 3 shown.
[0051] The components of the auxiliary phase alloy in each embodiment of Examples 1-5 are the same, while the components of the main phase alloy in each embodiment are changed, wherein the mass percentage of the cerium element gradually increases, the mass percentage of the rare earth metal praseodymium-neodymium alloy component gradually decreases, and the total mass percentage of the cerium element and the praseodymium-neodymium alloy component remains unchanged. Five samples of the permanent magnets prepared in Examples 1-5 are randomly taken out to detect the residual magnetism B r And coercivity H cj , and is represented by Table 1; where B r is the remanence, kGs is the magnetic field strength unit kilogauss, H cj is the intrinsic coercive force of the permanent magnet, and kOe is the magnetic field intensity in kilo-Oersteds.
[0052] Table 1: Remanent magnetism B of each sample block detected in Examples 1-5r Range and coercivity H cj scope;
[0053] The process conditions of Comparative Examples 8-12 are consistent with those of Examples 1-5, and the rare earth permanent magnets are prepared by the dual alloy process. The main phase alloy composition is consistent with that of Examples 1-5, except that the auxiliary phase alloy composition is different. The auxiliary phase alloy composition of Comparative Examples 8-12 is PrNd 45 Fe 45 Ga5, does not contain cobalt element, the mass percentage of iron element is 45%, and the total mass percentage of iron element and cobalt element in the embodiment is 45%, that is, the corresponding mass percentage of iron element in comparative examples 8-12 replaces the cobalt element in the corresponding embodiment, and 5 samples of the permanent magnets prepared in comparative examples 8-12 are randomly taken out to detect the remanence and coercive force H cj , as shown in Table 2; Table 2: Remanent magnetism B of each sample block detected in Comparative Examples 8-12 r The range and coercivity H cj scope;
[0054] It can be seen from Table 1 that compared with Comparative Examples 8-12, the residual magnetism B in Examples 1-5 r and coercivity H cj All of them are improved, especially the intrinsic coercive force. Specifically, when the cerium content is 6-12%, the intrinsic coercive force reaches 13.64-14.95kOe. Even when the cerium content is as high as 20%, the intrinsic coercive force reaches 10.56-10.73kOe. Compared with the comparative example 11 when the cerium content is 12%, the remanence and intrinsic coercive force are not much different. It can be seen that on the basis of ensuring the magnetic properties, by adding cobalt to the auxiliary phase alloy, the use of cerium can be effectively improved, and the use of part of rare earth elements can be replaced.
[0055] By comparing Table 1 and Table 2, it can be seen that under the same process conditions, the addition of cobalt element in the auxiliary phase alloy can effectively improve the intrinsic coercive force of the permanent magnet. When the cerium content continues to increase, the cobalt element can change the valence state of the cerium element, thereby reducing the precipitation of CeFe2 phase, avoiding the deterioration of magnetic properties, and maintaining higher magnetic properties of the permanent magnet.
[0056] Focus on combining Figure 1-2 As shown in the figure, Figure 1Schematic diagram of the microstructure of comparative example 10, from left to right are a grayscale image, a highlighted image of the Fe element, and a highlighted image of the Ce element. The red in the highlighted image of the Fe element is the Fe element, the light blue in the highlighted image of the Ce element is the Ce element, and the clustered part pointed by the arrow is the CeFe2 phase. Figure 2 The microstructure diagram of Example 3 is shown in the same manner as Figure 1 It is consistent and will not be repeated. It can be seen that under the same process conditions, in the permanent magnet containing cobalt element prepared in Example 3, the volume proportion of CeFe2 phase is significantly reduced, and the light blue Ce element diffuses more widely, and the Ce element content in the main phase is increased, which further illustrates that the addition of Co element through the dual alloy process can promote the Ce element to enter the main phase, promote the change of the valence state of the Ce element, and make the permanent magnet have high coercive force.
[0057] Focus on combining Figure 3-4 As shown, Figure 3 Schematic diagram of the microstructure of comparative example 12, from left to right are a grayscale image, a highlighted image of the Fe element, and a highlighted image of the Ce element. The red in the highlighted image of the Fe element is the Fe element, the light blue in the highlighted image of the Ce element is the Ce element, and the clustered part pointed by the arrow is the CeFe2 phase. Figure 4 The microstructure diagram of Example 5 is shown in the same manner as Figure 3 The contents of Ce in the main phase alloy components of Comparative Example 12 and Example 5 are consistent and will not be repeated. It can be seen that under the same process conditions, the permanent magnet containing no cobalt element prepared in Comparative Example 12 without adding Co element shows a large amount of Ce element enriched in the grain boundaries, and the grain boundaries are distributed in clusters, while in the permanent magnet containing cobalt element prepared by adding Co element in Example 5, the grain boundary agglomeration phenomenon is significantly reduced, and the proportion of CeFe2 phase in the grain boundary phase is significantly reduced.
[0058] In addition, the main phase alloy composition of Example 3 and Example 6-7 is the same, and the auxiliary phase alloy composition is different, which is manifested in that the content of cobalt and iron in the auxiliary phase alloy is different, but the total mass percentage of cobalt and iron in the two examples is the same. Five samples of the permanent magnets prepared in Example 3 and Example 6-7 are randomly taken out to detect the residual magnetism B r And coercivity H cj , and is represented by Table 3; Table 3: Remanent magnetism B of each sample block detected in Example 3 and Examples 6-7 r Range and coercivity H cj scope;
[0059] It can be seen from Table 3 that when the cerium content is 10%, as the cobalt content in the auxiliary phase alloy increases, the coercive force H of the permanent magnet prepared by the dual alloy process increases. cj It gradually becomes larger, which further shows that the addition of cobalt element can effectively inhibit the precipitation of CeFe2 phase, avoid the deterioration of the magnetic properties of the permanent magnet, and effectively increase the cerium element to replace part of the rare earth elements.
[0060] Comparative Example 1-7 does not adopt the dual alloy process to prepare the rare earth permanent magnet, but directly uses the components of the mixed powder formed by mixing in step 2 of Example 1-7 to prepare the permanent magnet, and then forms the permanent magnet after smelting, orientation pressing, isostatic pressing, sintering and heat treatment, and then randomly takes out 5 samples from the permanent magnet to detect the remanence and intrinsic coercive force, as shown in Table 4; Table 4: Remanent magnetism B detected for each sample block in Examples 1-7 and Comparative Examples 1-7 r Range and coercivity H cj scope;
[0061] It can be seen from Table 4 that the performance of the permanent magnets prepared in Examples 1-7 is better than that of the permanent magnets prepared in Comparative Examples 1-7, especially the intrinsic coercive force is about 1 kilo-oersted higher on average, indicating that the high-cerium and high-cobalt content magnets prepared by the dual alloy method have better comprehensive magnetic properties.
[0062] The above description is only a preferred embodiment of the present invention and is not a limitation on the design of this case. Any equivalent changes made based on the design key of this case shall fall within the protection scope of this case.
Claims
1. A cerium-containing high coercivity rare earth permanent magnet, characterized in that: The permanent magnet has a composition of RE in terms of mass percentage. a N b Fe 100-a-b-c-d Co c B d , RE is a combination of two or more of the rare earth elements lanthanum, cerium, praseodymium, and neodymium, and must contain cerium, the mass percentage of which is not less than 6%, N is a combination of one or more of aluminum, copper, gallium, and zirconium, Fe is iron, Co is cobalt, and B is boron; Among them, a, b, c and d respectively satisfy the following relationships: 26≤a≤35, 0.2≤b≤6.7, 0.2≤c≤7.5, 0.85≤d≤1.
3.
2. A method for preparing a cerium-containing high-coercivity rare earth permanent magnet is used to prepare the cerium-containing high-coercivity rare earth permanent magnet according to claim 1, characterized in that: The permanent magnet is prepared from two raw materials, a main phase alloy and an auxiliary phase alloy, in the form of a double alloy. The main phase alloy contains cerium elements, and the auxiliary phase alloy contains cobalt elements.
3. The method for preparing a cerium-containing high coercivity rare earth permanent magnet according to claim 2, wherein the main phase alloy has a composition of (Ce a1 RE' b1-a1 ) b1 Q bal M c1 B d1 , Ce is cerium, RE' is one or more of the rare earth elements lanthanum, cerium, praseodymium, and neodymium, Q is iron, M is one or more of gallium, aluminum, copper, zirconium, and cobalt, and B is boron; in, a1, b1, c1, and d1 satisfy the following relationships respectively: 6≤a1≤20, 28≤b1≤31, 0≤c1≤2, 0.9≤d1≤1.1, bal is expressed as the remainder, bal=100- b1- c1- d1, the content of cerium element is a1, the content of RE' is b1- a1, and the sum of the contents of Ce and RE' is b1.
4. The method for preparing a cerium-containing high coercivity rare earth permanent magnet according to claim 2, wherein the auxiliary phase alloy has a composition of RE in terms of mass percentage. a2 Q" b2 M" c2 , RE" is one or more of the rare earth elements lanthanum, cerium, praseodymium, and neodymium, Q" is one or two of the elements iron and cobalt, and Q" contains at least cobalt, and M" is one or more of the elements gallium, aluminum, copper, and zirconium; in, a2, b2, c2 respectively satisfy the following relations: 15≤a2≤45, 25≤b2≤55, 5≤c2≤15, a2+b2+c2=100.
5. The method for preparing a cerium-containing high coercivity rare earth permanent magnet according to claim 2, characterized in that: The permanent magnet comprises (RE', Ce)2Fe 14 B main phase, (RE H , Ce)2(Fe, Co) 14 B main phase and rare earth-rich phase; Wherein, the main phase alloy contains the (RE', Ce)2Fe 14 B main phase, the main phase alloy and the auxiliary phase alloy are prepared in the form of a dual alloy, and the grain boundary is reconstructed to form the (RE H , Ce)2(Fe, Co) 14 B main phase and rare earth-rich phase, RE H Represents the rare earth elements contained after grain boundary reconstruction.
6. The method for preparing a cerium-containing high coercivity rare earth permanent magnet according to claim 2, further characterized in that it comprises the following steps: S1: preparing a main phase alloy ribbon through a vacuum rapid solidification process, and then preparing the main phase alloy ribbon into a main phase alloy powder through a hydrogen crushing and air flow grinding process, wherein the vacuum degree of the vacuum rapid solidification process is ≤5.0-2Pa; The auxiliary phase alloy is subjected to a vacuum rapid solidification process to prepare an auxiliary phase alloy ribbon, and then the auxiliary phase alloy ribbon is prepared into an auxiliary phase alloy powder by hydrogen cracking and air flow grinding, wherein the vacuum degree of the vacuum rapid solidification process is ≤5.0-2Pa; S2: uniformly mixing the main phase alloy powder and the auxiliary phase alloy powder under the protection of an inert gas to form a mixed powder, wherein the auxiliary phase alloy powder accounts for 3% to 10% of the total mass of the mixed powder; S3: Orienting and molding the obtained mixed powder in a magnetic field of 1.5-2.5 T to obtain a green body; S4: vacuum-packaging the obtained green body, cold isostatically pressing at 180-220 MPa, and placing it in a vacuum sintering furnace for sintering and heat treatment to obtain the permanent magnet.
7. The method for preparing a cerium-containing high coercivity rare earth permanent magnet according to claim 6, characterized in that: The sintering temperature is 950-1080° C., and the sintering time is 3-5 hours.
8. The method for preparing a cerium-containing high coercivity rare earth permanent magnet according to claim 6, characterized in that: The primary aging temperature range of the heat treatment is 700-920° C., and the time is 3-5 hours. The secondary aging temperature range of the heat treatment is 400-700° C., and the time is 3-5 hours.
9. The method for preparing a cerium-containing high coercivity rare earth permanent magnet according to claim 6, characterized in that: The thickness of the main phase alloy strip is 0.2-0.5 mm.
10. The method for preparing a cerium-containing high-coercivity rare earth permanent magnet according to claim 6, characterized in that: The main phase alloy powder has a size of 3 to 5 μm, and the auxiliary phase alloy powder has a size of 3 to 5 μm.
Citation Information
Patent Citations
Corrosion-resistant cerium-contained rare earth permanent magnet material and preparation method therefor
CN105931784A
High-toughness and high-coercive-force Ce-containing sintered rare-earth permanent magnet and preparation method thereof
CN108922710A
Fabrication method of high-coercivity Nd-Ce-Fe-B sintered magnet
CN108922714A
Cerium-iron-aluminum alloy, cerium-containing rare earth permanent magnet and manufacturing method thereof
CN111210961A
Cerium-iron-boron permanent magnet material and preparation method thereof
CN118942826A
Cited By
High-coercivity neodymium-iron-boron magnet and preparation method thereof
CN121260662A